Improving Indonesia’s Palm Oil Sustainability Through Financing: A Study on Disconnects and Potential Policy Solutions - Wahid, Wewin Wira Cornelis; Aprillia, Kanaya Ratu; Ramatia, Deasy; Setiawati, Nadya; Subkhi, Syukron; Swastika, Abdul Baits Dehana Padma; Rianawati, Elisabeth (UI Scholars Hub, 2024)
The European Union’s Second Renewable Energy Directive (RED II) has brought significant discourse on Indonesia’s palm oil sector. Following growing global initiatives in sustainable palm oil, Indonesia should focus on improving palm oil sustainability rather than rely on markets that accept the country’s palm oil as is. However, there are still disconnects in sustainable palm oil, especially in the financial aspects. Therefore, this research aims to identify significant disconnects and propose solutions within a financing context. The disconnects include the absence of mandatory policies for sustainable palm oil financing, limited adoption of sustainability policies by smaller financiers, concerns about ISPO robustness, inadequate financial incentives for smallholders in certification, challenges in accessing finance for smallholders, and administrative barriers to accessing replanting funds. To address these disconnects, the research proposes several solutions. First, to mandate sustainable palm oil financing in POJK 51 and the green taxonomy. Second, provide capacity building for local banks and mandate measures to gradually finance sustainable palm oil. Third, strengthening ISPO by adopting global measures, adopting robust means of verification, and implementing further requirements to enable traceability. Fourth, provide incentives for certification to smallholders, alongside expanding the CPO Fund’s role to help finance smallholder certification and legalization. Fifth, upscale schemes of step up loans and successful practices of plasma programs for smallholder palm oil. Sixth, simplify CPO Fund requirements for replantation. Overall, this research hopes to provide recommendations on governing sustainable palm oil through financing, particularly through insights on what policies are needed.